Integrasi Kewirausahaan dan Pendidikan Islam dalam Peningkatan Kesejahteraan Masyarakat - Luqman Alfattah; Bambang Mursito; Sarsono (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The integration of Islamic education with entrepreneurship is an effort to bring about changes in people's quality of life, attitudes and decision making. Especially for students studying at Islamic boarding schools, this knowledge is very important to learn. In this research, researchers used a qualitative descriptive approach using observation, interviews and documentation. Determining informants using the proportional sampling method. This research found: 1) integration of entrepreneurship and Islamic education is needed to improve the welfare of the community in that location because: a) community leaders are very steeped in religion so they always prioritize religion in everything. b) portrait of the diversity of livelihoods of the surrounding community; c) to establish social, religious and entrepreneurial relations with the surrounding community; 2) implementation of the integration of entrepreneurship and Islamic education in improving the welfare of the Sangen Modern Islamic Boarding School community is carried out by implementing entrepreneurship programs in the fields of fisheries, agriculture and cooperatives/canteens within the Islamic boarding school. Keywords: Integration; Entrepreneurship; Islamic education; Well-being Public